Solo scrum in bureaucratic organization: A case study from Thailand - Lachana Ramingwong (2018)
© Springer Nature Singapore Pte Ltd. 2018. Scrum becomes the most popular Agile methodology due to its simple principles and ability to adapt to various environment. It offers flexibility to software development and allows teams to have control over the course of development. Although there were several successful attempts of Scrum adoption throughout different parts of the world, there are still challenges in implementing Scrum in bureaucratic organizations. This paper presents findings from a pilot adoption of Solo Scrum, which a single developer employed and adapted Scrum practices in a software project in a Thai bureaucratic organization where several issues turn to be obstacles to the adoption including bureaucratic structure, layers of approvals, culture, etc. Organizational culture is found to be a major obstacle in this case study. Conflicts and solutions are discussed. The challenges and issues related to Mum effects are also addressed. Adoption of Agile methodologies in Thailand is still new topics, which needs to be studied further.